Agrifood system in India - state factsheet: Bihar - Pal, Barun Deb; Ajmani, Manmeet Singh; Thurlow, James; Pauw, Karl (International Food Policy Research Institute, 2023)
This factsheet provides a brief description of the economic structure and the size of the agrifood system of Bihar, an Indian state. The agrifood system comprises primary agriculture, food processing, agrifood trade, food services, and input supplies. We have constructed a multistate social accounting matrix (SAM) for the year 2017/18 to understand the size of Bihar’s agrifood system in comparison with the rest of India.